The Emerging Obstacles in the Provision of Healthcare Supply Chain Services - McBride, Maurice L. (Cybersecurity and Innovative Technology Journal, 2024)
The COVID-19 pandemic has exposed flaws in the healthcare supply chain, including shortages, delays, and logistical issues. Key problems include inadequacies in resilience, visibility restrictions, cost management obstacles, integration barriers, unstated costs, and disparities in inclusivity. This research uses secondary data analysis to analyze findings from academic literature, industry reports, and case studies. It emphasizes the value of resilience and visibility, suggesting investing in blockchain, AI, and IoT technology for increased transparency and risk management. The report also emphasizes the need for proactive solutions, such as data analytics for improved supply chain visibility, hybrid inventory strategies for cost control, and stakeholder engagement for smooth integration. Integrating procurement, transportation, storage, and production, addressing misuse and hidden costs, and fostering inclusion are critical aspects of enhancing the healthcare supply chain.